Reining in the Executive? Delegation, Evidence, and Parliamentary Influence on Environmental Public Policy. (August 2013) - Russel, Duncan; Turnpenny, John; Rayner, Tim
With this paper we explore the potential of committees in parliamentary systems of government to influence environmental public policy making. We draw on delegation theory to argue that parliamentary committees are crucial ex post mechanisms used by the legislature (the principal) to monitor the activities of the executive (its agent). To examine this relationship in depth, we focus on the United Kingdom's Environmental Audit (select) Committee (EAC), which is an innovation as the world's first cross-cutting environmental parliamentary committee. We find that delegation theory provides fresh insights into the relationship between the EAC, the legislature, the executive, and the wider public. We find that an incomplete system of delegation in the United Kingdom has left an accountability deficit, meaning that the EAC's ability to exert influence on the executive's environmental policy is limited.